INTERNALIZATION OF ISLAMIC RELIGIOUS EDUCATION VALUES IN THE BOOK OF ADABUS SULUKIL MURID IN SHAPING THE CHARACTER OF SANTRI - Ahmad Reza Fahlefi; Muhammad Yusron Maulana El-Yunusi; Dewi Wulandari (Journal Analytica Islamica, 2024)
This research is based on the negative impact of technological progress, namely the decline in character, therefore it is necessary to internalize values. This research is located at the Darul Ulum Islamic Boarding School, which is one of the Islamic educational institutions that has the characteristics of deepening the yellow book. However, he also left formal education located in Moncek Tengah Village, Lenteng District, Sumenep Regency, East Java. The purpose of this study is to find out the process of internalization and values of Islamic education in the book of Idabus Sulukil Murid and the character of students at the Darul Ulum Moncek Tengah Lenteng Sumenep Madura Islamic boarding school. The method used is qualitative. The place of research was carried out at the Darul Ulum Moncek Tengah Lenteng Sumenep Islamic Boarding School, Madura. The data sources used are in the form of Primary Data Sources and Secondary Data Sources. The data collection techniques used are observation and interviews. The researcher used miles, Huberman and saldana data analysis techniques, namely data condensation, data presentation and conclusion drawn. The results of the study show that the formation of the character of religious, disciplined and independent students, when internalizing the values of Islamic education in the book Risalah Adabus Sulukil Murid in the form of the values of faith, ubudiyah and akhlaq through the stages of transformation, transaction and transinternalization. The contribution of research results to scientific development is to provide empirical evidence about the importance of internalizing Islamic educational values in shaping the character of students who are religious, disciplined, and independent. This can be a reference for the development of character education curriculum in Islamic boarding schools.